TRANSFORMASI BUDAYA KERJA DI LINGKUNGAN PEMERINTAH KABUPATEN PENAJAM PASER UTARA MELALUI PENDEKATAN SIX THINKING HATS (WORK CULTURE TRANSFORMATION IN PENAJAM PASER UTARA REGENCY THROUGH SIX THINKING HATS APPROACH) - Aziza, Tri Noor (Pusjar SKPP Lembaga Administrasi Negara, 2015)
Nowadays, work culture transformations have become the trend setter for local governments in enhancing the performances of their apparatus. Occasionally, aparatus' old mind and culture that has been set for a long time make it a challenge to transform it into the apparatus with high integrity, high productivity, high performance, and good personality. Strong will and deliberate efforts which are combined with sustainable evaluations are needed to be able to achieve these goals. This situation must be implemented in comprehensive ways which must be well planned, well structured and sustainable. Besides that, it must also be supported with tremendous discipline, great resources and periods of time. This articel tries to describe the implementation of work culture transformation which is implemented by Penajam Paser Utara (PPU) Region starting from its values formulation, implementation. finally, with the implementation of work culture transformation, it is greatly expected that a better transformation milestone can be attained by PPU.Keywords : Transformation, Work Culture, Organization Transformasi budaya kerja saat ini tampaknya telah menjadi trend setter bagi pemerintah daerah dalam upaya meningkatkan kinerja aparaturnya. Namun ternyata tidak mudah dalam merubah pola pikir dan budaya aparatur lama yang telah tertanam dan berakar kuat menjadi aparatur yang berintegritas, produktif, berkinerja dan berkepribadian tinggi. Diperlukan tekad yang kuat, upaya yang tepat dan evaluasi secara terus menerus. Hal ini harus berjalan secara terencana, terstruktur, komprehensif dan berkelanjutan serta membutuhkan komitmen serta kedisiplinan yang luar biasa, sumber daya yang besar dan waktu yang panjang. Tulisan ini mendeskripsikan pelaksanaan transformasi budaya kerja yang dilakukan Pemerintah Kabupaten Penajam Paser Utara (PPU) dari tahapan perumusan nilai-nilai, implementasi, akhirnya, dengan dilaksanakannya transformasi budaya kerja ini, diharapkan menjadi tonggak dasar dalam upaya perubahan yang lebih baik lagi bagi Pemkab PPU.Kata Kunci : Transformasi, Budaya Kerja, Organisasi